2016
DOI: 10.1016/j.tips.2015.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Protein S -Nitrosylation as a Therapeutic Target for Neurodegenerative Diseases

Abstract: At physiological levels, nitric oxide (NO) contributes to the maintenance of normal neuronal activity and survival, thus serving as an important regulatory mechanism in the central nervous system. In contrast, accumulating evidence suggests that exposure to environmental toxins or the normal aging process can trigger excessive production of reactive oxygen/nitrogen species (such as NO), contributing to the etiology of several neurodegenerative diseases. Here we highlight protein S-nitrosylation, resulting from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
126
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(130 citation statements)
references
References 94 publications
(120 reference statements)
2
126
0
2
Order By: Relevance
“…It has been shown that in degenerative conditions characterized by oxidative stress, increased levels of NO lead to aberrant S-nitrosylation of proteins that contributes to the pathology of the disease [25]. Excessive liberation of NO and enhanced S-nitrosylation affects the mitochondrial function, proteostasis, transcriptional regulation, synaptic activity, and cell survival [26]. In the present work, the level of intracellular NO in PC12 cells was remarkably increased by SNP.…”
Section: Discussionsupporting
confidence: 53%
“…It has been shown that in degenerative conditions characterized by oxidative stress, increased levels of NO lead to aberrant S-nitrosylation of proteins that contributes to the pathology of the disease [25]. Excessive liberation of NO and enhanced S-nitrosylation affects the mitochondrial function, proteostasis, transcriptional regulation, synaptic activity, and cell survival [26]. In the present work, the level of intracellular NO in PC12 cells was remarkably increased by SNP.…”
Section: Discussionsupporting
confidence: 53%
“…The assay mixture contained 200 µM NADP + and varying concentrations of 6-phosphogluconate (5,10,25,50, 75, 100, 250 or 500 µM); the assay was initiated by the addition of 20 nM 6PGD. For 6PGD GSNO-treated samples, the assay was initiated with 600 nM enzyme.…”
Section: Pgd Assaymentioning
confidence: 99%
“…COMT assay: The activity assay buffer was 100 mM sodium phosphate at pH 7.6 and 1.2 mM MgCl 2 . The assay mixture contained 1 mM SAM with varying concentrations 3,4-dihydroxybenzoic acid (DHBA) (5,10,15,20,40,60 or 100 µM) and was pre-incubated for 2-3 min at 37 °C before enzyme addition. The assay was initiated by the addition of 200 nM COMT in a 450 µL Eppendorf tube and incubated at 37 °C.…”
Section: Pgd Assaymentioning
confidence: 99%
“…Excessive NO generation and aberrant protein S-nitrosylation contribute to the pathogenesis of neurodegeneration (Nakamura & Lipton 2016). In particular, S-nitrosylated GAPDH has been shown to mediate the stress signaling cascade associated with neurotoxicity (Nakamura et al 2015).…”
Section: Resultsmentioning
confidence: 99%